2018
DOI: 10.1094/mpmi-03-18-0071-r
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharide Induces Resistance toPseudomonas syringaepv.tomatoDC3000 inArabidopsis thalianaby Activating Both Salicylic Acid– and Jasmonic Acid–Mediated Pathways

Abstract: Chitosan oligosaccharide (COS) is an effective plant immunity elicitor; however, its induction mechanism in plants is complex and needs further investigation. In this study, the Arabidopsis-Pseudomonas syringae pv. tomato DC3000 (hereafter called DC3000) interaction was used to investigate the induction effect and the underlying mechanisms of COS. COS is effective in inducing resistance to DC3000 in Arabidopsis, and our results demonstrate that treatment with COS 3 days before DC3000 inoculation provided the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 61 publications
1
35
2
Order By: Relevance
“…The functions of SA and JA in plant immunity could be antagonistic [49,50]. However, literature has shown that SA and JA could cooperate with each other and function synergistically in plant immunity [51][52][53]. In general, to defend against the infections of the necrotrophic and biotrophic pathogens, ABA is a negative regulator in plants [49].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of SA and JA in plant immunity could be antagonistic [49,50]. However, literature has shown that SA and JA could cooperate with each other and function synergistically in plant immunity [51][52][53]. In general, to defend against the infections of the necrotrophic and biotrophic pathogens, ABA is a negative regulator in plants [49].…”
Section: Discussionmentioning
confidence: 99%
“…7). Recent studies have shown that CSOSs induce a series of immune responses to alleviate virus and bacterial infection in Arabidopsis (64,65). These results indicate that Arabidopsis cells do perceive CSOS in a CERK1-independent manner.…”
Section: Ctos As a Model Fungal Mamp To Study Fungus-induced Stomatalmentioning
confidence: 81%
“…In particular, chitosan has been investigated in a wide spectrum of drug delivery systems including pharmaceutical, food industry and agriculture applications thanks to its biocompatibility, antibacterial and plant-immunity eliciting properties [16][17][18]. The antimicrobial efficacy of chitosan is known for a broad range of pathogens [19,20]; in vitro biocidal activity [21] and an in-field efficacy [22] was observed for P. syringae pv. actinidiae.…”
Section: Phytopathogens Control Strategies: the Cases Of Xylella Fastmentioning
confidence: 99%